Model of Improved Set Covering Location Problem in Determining The LRT Musi Emas Feeder Stops: Route LRT DJKA Station - Plaju Terminal - Octarina, Sisca; Puspita, Fitri Maya; Yuliza, Evi; Indrawati; Tasiah, Mawar (Science and Technology Indonesia, 2025)
This study aims to determine the optimal location of the LRT Musi Emas Feeder stops Corridor 5 in conjunction with the LRT DJKA Station-Plaju Terminal route. Light Rail Transit (LRT) is a rapid transit system that employs an integrated rail crossing model. At present, the LRT remains a primary mode of daily transportation for the residents of Palembang. One of the initiatives undertaken by the government to facilitate the utilization of LRT transportation is the provision of passenger transportation (feeder services). The positioning of the feeder stops remains suboptimal and needs more integration with existing public facilities. The distance between the stop locations is highly variable, with some nearby and others at considerable distances. This issue is addressed through the formulation of the Set Covering Problem (SCP) model, which encompasses the Set Covering Location Problem (SCLP) and Maximal Covering Location Problem (MCLP) models, as well as the development of the Improved SCLP model. The SCP model yields four optimal stop locations, which are significantly distant from the actual conditions at the site. In contrast, the Improved SCLP model identifies 48 optimal feeder stops mapped using Geographic Information System (GIS) software. This map of feeder stops could inform the Palembang City Transportation Agency’s efforts to develop an integrated transportation management system.